Design and analysis of RF low noise amplifier - Tan, Sean (Nanyang Technological University, 2021)
This project studies the process of designing and analysing a narrowband Low Noise Amplifier (LNA) using a Field Effect Transistor (FET) at an operating frequency of 2.4 GHz. To provide a clearer understanding of the entire design procedure, design theories and formulas were also explained in detail throughout this paper. The goal of this project is to achieve desirable performance on various parameters such as stability factor, gain, noise figure as well as input and output reflection coefficient. The design and simulation for most part of this project is done through the Advanced Design System (ADS) software and the simulated result of the completed LNA circuit showed that all requirements that were set beforehand were met.